2000
DOI: 10.1007/s005200050005
|View full text |Cite
|
Sign up to set email alerts
|

A survey of mouth pain and dryness in patients with advanced cancer

Abstract: An 11-item face-to-face survey was conducted in 99 consecutive patients with advanced cancer to determine the prevalence, intensity, reporting and treatment, presumed cause(s), and importance of mouth pain and dryness. Sixteen of the 99 patients (16%) reported experiencing mouth pain at a mean intensity corresponding to 5.5 +/- SD 2.21 on a 0 (no pain) to 10 (worst possible pain) numerical scale, and 88 (88%) patients reported dry mouth at a mean intensity corresponding to 6.2 +/- SD 2.21. Nine (56%) of the 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 13 publications
(19 reference statements)
3
28
0
Order By: Relevance
“…In patients attending a palliative care outpatient clinic, the prevalence of dry mouth was even higher to that reported in this survey [16]. Data were even more relevant in another study in which 88 % of palliative care patients reported dry mouth, with an intensity similar to that found in this study [13]. Dry mouth was one of the symptoms that presented a tendency to persist or to worse after admission to a palliative care unit [17].…”
Section: Dry Mouthsupporting
confidence: 57%
See 2 more Smart Citations
“…In patients attending a palliative care outpatient clinic, the prevalence of dry mouth was even higher to that reported in this survey [16]. Data were even more relevant in another study in which 88 % of palliative care patients reported dry mouth, with an intensity similar to that found in this study [13]. Dry mouth was one of the symptoms that presented a tendency to persist or to worse after admission to a palliative care unit [17].…”
Section: Dry Mouthsupporting
confidence: 57%
“…Pain may be of concern, possibly limiting the ingestion of food and fluids. Sixteen percent of patients reported mouth pain at a mean intensity of 5.5 on a numerical scale from 0 to 10 [13]. As a consequence, oral cavity should be carefully assessed to treat the local condition, while eliminating eventual reversible factors, and pain management should be optimized.…”
Section: Mucositismentioning
confidence: 99%
See 1 more Smart Citation
“…This emphasises that hospital and dental staff should gather data on patient experiences of oral symptoms in addition to performing clinical examinations. This has also been emphasised by Dodd et al [5], who demonstrated that the medical record severely underdocumented the prevalence of mucositis compared with an interview, and by Oneschuk et al [28], who found that mouth pain and mouth dryness were underreported by patients with advanced cancer. However, clinical examinations and tests provide important indicators of the extent of oral complications and should be used as a complement to data on patient experiences.…”
Section: Discussionmentioning
confidence: 90%
“…This is of major importance as patients tend to underreport mouth pain and dryness, with the result that these complaints are inadequately represented in outcomes and interpretation of clinical studies [44]. These problems have led to several attempts to define "more valid" xerostomia outcome ratings covering the broad range of salivary properties [14,37].…”
Section: Introductionmentioning
confidence: 99%